To the question of folk traditions in the Russian romantic lyrics (based on the "Russian Song" of E. A. Baratynsky) - PATROEVA, NATALYA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper gives a linguo-stylistic analysis of the poem of E.A. Baratynsky "Russian Song" showing how this work reflects the tradition of folklore stylizations peculiar to romantic lyrics. The paper also analyzes lexical, grammatical and metric features ofthe genre "song", as well as the problem of the sources, literary influences and intertextual elements in the poem of Baratynsky in the aspect of biography and creative evolution of the author.
Keywords: literary folklorism, folklore stylization, Russian song, Romanticism, Russian lyrics